PRODUKTIVITAS BIOMASSA DAN LAJU PERTUMBUHAN RUMPUT LAUT Eucheuma cottonii DI PERAIRAN WAEL SERAM BAGIAN BARAT PROVINSI MALUKU - Johanis Fritzgal Rehena (The East Java Biological Society, 2009)
Biomass productivity and growth rate of Eucheuma cottonii has been done during three cultivation periods of the year 2008 in water territory Wael, in the west of Seram regency. Research of sea grass was conducted by float raft method (floiting method) systems monoline. Statistical design used Factorial Pattern Completely Randomized Design 3 × 3 × 2. Cultivation period as factor A consisted of A1 (period I), A2 (period II), and A3 (period III). The result of the analysis showed that cultivation period (factor A) and also initial weight (factor B) gave a real response to growth rate Eucheuma cottonii, and so do second interaction of factor (AB) gave real response. Average of biomass productivity during three cultivation periods of each different initial number weighing ranged from 108.65–664.76 gram/sea grass with daily growth number ranged from 2.15–6.86% / day